Post a New Question

trigonometry

posted by on .

Been trying this forever so it says: Simplify 1+sin2x+cos2x/1+sin2x-cos2x

ive tried this problem so many times I need help with it...

  • trigonometry - ,

    I believe you mean

    (1+sin2x + cos2x)/(1+sin2x - cos2x)

    = (sin^2 x + cos^2 x + 2sinxcosx + cos^2 x - sin^2x)/(sin^2 x + cos^2 x + 2sinxcosx - cos^2x + sin^2x)
    = (2cos^2 x + 2sinxcosx)/(2sin^2 x + 2sinxcosx)
    = 2cosx(cosx+sinx)/((2sinx(sinx+cos))
    = 2cosx/2sinx
    = cot x

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question